The Influence of Globalization in Indonesia's National Legal Order - Christwan Christwan; Salmon Ginting (CV. Publikasi Indonesia, 2025)
Globalization is not something that can be avoided by a country and will make significant changes in various sectors that can have potential and negative impacts. The changes that will and will definitely occur are in the legal order of a country, in this case Indonesia, although there is an adage that says